A study on the implementation of relationship management (supply chain management) in Malaysia construction industry - Chang, Ting Wai (2014)
Constructions project often suffer from poor performance such as project delayed, cost overruns, and quality defects. The major reason for the occurrence of poor performance comes from the deterioration of supply chain management. Few researchers have identified the influence of supply chain relationships on the construction project. Supply chain management is to enable the companies to ensure the business has the materials, information and financial resources it needs to produce quality goods and services in a timely manner (O'Brien et al., 2008). Delays, cost over budget, failure of a building, poor quality and others was caused by the poor performance of operating staffs and labours. There are few studies have addressed the influence of supply chain relationships on project performance in construction. In this study, a supply chain relationship is described by key indicators in ten areas: mutual objectives, commitment, trust, no - blame culture, joint working, communication, problem solving, risk allocation, performance measurement, and self- improvement. The objective of this research is to study the implementation of supply chain management in Malaysia construction industry and to investigate the challenges in implementing it. This research was conducted by collecting data through respondent from three types of company which are developer, consultant, and contractor. Both questionnaire and interview survey were used for data collection. After that, the data and information was analysed by using Microsoft Excel. Lastly, conclusions and recommendations have been done. From the results of the questionnaire, company did not provided SCM training courses due to financial issues is the main challenge in implementing SCM. The problems of poor performance can be reduced by improving and maintain good relationship between project parties. In addition, further study is needed so the effect of SCM on construction performance by emerging the key indicator of optimum performance by implementing the SCM in Malaysia construction industry can be achieved.